URGENSI MEMPELAJARI ULUMUL QUR’AN - Lutfi, Chairul; Zulfiqri, Muammar (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2022)
Ulumul Al-Qur'an is defined variously according to scholars, but generally refers to a set of sciences that study everything about the Al-Qur'an or discussion studies that cover various aspects of the Al-Qur'an. The scope of the Ulumul Qur'an is several subjects, such as Nuzul, Sanad, Ada' al-Qira'ah, Lafadz al-Qur'an, the meaning of the Qur'an and Law, and the meaning of the Qur'an and Lafadz. This qualitative research is library research. Ulumul Qur'an has several branches including the science of adab tilawat Al-Qur'an, the science of tajwid, the science of mawathin an-nuzul, the science of Tawarikh an-nuzul, the science of asbab an-nuzul, the science of qira'at, the science of gharib Al-Qur'an , the science of i'rab Al-Qur'an, and others. The conclusion of this research is that the urgency of studying the Ulumul Qur'an is to achieve a deep and accurate understanding of the messages of the Qur'an by referring to valid interpretations and explanations from trusted sources. From the historical aspect of the Al-Qur'an, a tool to help read and understand the Al-Qur'an, becomes the ultimate weapon in defending the existence and function of the Al-Qur'an, understanding the meanings of sentences and laws in the Al-Qur'an , and carry out instructions to achieve happiness in this world and the hereafter.